ASSET ALLOCATION:DIVERSIFICATION DAN REBALANCING SEBAGAI BAGIAN DARI PROSES PERENCANAAN KEUANGAN (Suatu Kajian Pustaka) - Vera Intanie Dewi (Bina Ekonomi, 2013)
Financial planning is the process of designing an investmentstrategy that can helps an individual to achieve financial goals. Asset allocation, diversification and rebalancing is a particularly important steps of investment strategy process. By doing asset allocation and diversification among a variety of different asset categories such as bonds,stocks,mutual funds and saving can helps minimize risk and maximize return. And the goal of rebalancing is to move the current asset allocation back in line to the originally planned asset allocationKeywords: Financial Planning, Asset Allocation,Diversification andRebalancing.